Advances in endovascular aneurysm management: flow modulation techniques with braided mesh devices. Issue 1 (25th March 2020) - Campos, Jessica K; Cheaney II, Barry; Lien, Brian V; Zarrin, David A; Vo, Chau D; Colby, Geoffrey P; Lin, Li-Mei; Coon, Alexander L
Abstract : Flow diverters and flow disruption technology, alongside nuanced endovascular techniques, have ushered in a new era of treating cerebral aneurysms. Here, we provide an overview of the latest flow modulation devices and highlight their clinical applications and outcomes.